Selection of authors, titles and writing a manuscript abstract - Akman, Tolga (Turk J Urol, 2013)
Title of the study, authors list and abstract are not only the most widely read parts in an article but also determine whether the remaining sections are worth to be read. The first author in an article should be the planner and performer of the research. Researchers who have actively conducted the study and written the manuscript should be sorted in the authors list according to the importance of their individual contribution. However, researchers who do not directly contribute to the study but take part in data collection process should not be included in the ideal authors list. The title should be comprised of a brief statement or one or two short sentences that best reflect the original and gripping aspects of the study. On the other hand, abstract should provide answers to the following questions in advance of reading the full text: Why this study was performed?, What was the procedure?, What was found?, and What were the outcomes? In this manuscript, writing of an abstract was reviewed in addition to author and title selection.